Challenges Faced by PH.D. Scholars and Supervisors During COVID-19 in Turkey and Pakistan - Sajjad Hussain, Madiha Naz, Safia Bibi, Hafiz Ali Raza, Heikki Ofori Opoku, Suliman Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
This study focuses on explicit written feedback from online supervisors to PhD supervisees regarding their performance delivered during the first wave of COVID-19. The impact of this exceptional circumstance on pupils' academic lives is wide-ranging. This situation has affected how students and teachers communicate. Given that online feedback and communication are new experiences for most students, the current study aimed to reveal the supervisee's and supervisors' perceptions of the communication and feedback process. The results show that professors and supervisors provide feedback on students' work and that teacher-student interaction is crucial for students' ability to improvise during performances. The outcome revealed several social, academic, and unexpectedly psychological challenges both supervisees and supervisors encountered when communicating online during COVID-19.